Influence of body composition and muscle power performance on multiple frequency speed of kick test in taekwondo athletes - Apollaro, G.; Panascì, M.; Ouergui, I.; Falcó, C.; Franchini, E.; Ruggeri, P.; Faelli, E. (Sports, 2024)
The Multiple Frequency Speed of Kick Test (FSKTmult) is used to investigate which characteristics are necessary for, contribute to, or limit the ability to repeat high-intensity intermittent efforts in taekwondo. This cross-sectional study investigated the relationship between anthropometric and body composition characteristics, muscle power performance, and sport-specific anaerobic performance. Nineteen black belt taekwondo athletes (mean ± SD age: 17.2 ± 2.4 years) volunteered to participate. Anthropometric and body composition characteristics (i.e., body height (BH), body mass (BM), fat mass (FM), body fat (BF%), and muscle mass (MM)) and physical performance (squat jump (SJ), countermovement jump (CMJ) tests, and FSKTmult) were assessed. Data were analyzed with correlation coefficients and simple linear regression. The statistical significance was set at p < 0.05. The total number of kicks in FSKTmult (FSKTtotal) was significantly and positively correlated with MM (r = 0.521, R2 = 0.27, p < 0.05) and negatively with BF% (r = -0.499, R2 = 0.25, p < 0.05). The FSKTtotal was significantly and positively correlated with SJ (r = 0.520, R2 = 0.27, p < 0.05) and CMJ (r = 0.508, R2 = 0.26, p < 0.05) performance. Body composition optimization, with appropriate physical training and dietary planning, is relevant in taekwondo as the improvement in the ability to repeat high-intensity intermittent efforts depends on MM, and its worsening on BF%. Lower limb muscle power positively influences the ability to repeat high-intensity intermittent efforts. Therefore, training programs should emphasize ballistic and plyometric exercises.